Conceptual Model of Schoolchildren’s Financial Literacy and Financial Capability Formation in the course of Mathematics - Safronova, Tatiana (2020)
Social and economic transformation in modern society, the sophistication of world financial systems, and, as a result, changes in the hierarchy of human needs, conceptually new interests and requirements of the entire society have determined the relevance of the issue on the formation of financial literacy and financial capability of schoolchildren. Awareness of the necessity to address the issue leads to the creation of various strategies, projects, and curricula. The key methods of research include the following: analysis of academic literature that discloses the meaning of financial literacy as a multivariate concept; analysis of psychological-pedagogical literature and scientific research results of native and foreign authors in the field of improvement of the financial culture of children and youth; modeling of the conceptual model of financial literacy and financial capability formation of comprehensive schoolchildren in the course of mathematics. The authors have developed the conceptual model of the formation of financial literacy and financial capability of comprehensive schoolchildren in the course of mathematics. This model is based on interrelated scientific principles, unified as a single system, and integrated methodological approaches (system-activity, competence-based, synergetic, simulation, contextual, social, and cultural), has its own goal, objectives, means for achieving them, predicted outcome of the research. All the components of the model are considered as interdependent. The model is theoretically, methodologically and technically justified. Its quality is determined by its completeness, concreteness, tenability and feasibility, optimality of the mix of mathematical and economical components. The practical implementation of the authors’ conceptual model could contribute to the mobilization of resources of schoolchildren’s personal development and further efficient utilization of these resources in different fields of activity that is, therefore, could lead to the growth of the society’s “vital capacity”. The reported study was funded by RFBR, project number 19-413-480013.